Prevalence of carbohydrate metabolism disorders in patients with end-stage renal disease on hemodialysis therapy - T. N. Markova; V. O. Yavorskaya (Сахарный диабет, 2022)
There are quite a lot of scientific works today dedicated to the role of disorders carbohydrate metabolism (DCM) in the development of end-stage renal disease (ESRD), at the same time, the influence of chronic kidney disease (CKD) on the development of carbohydrate disorders remains insufficiently studied, especially in patients on renal replacement therapy (RRT). The annual steady increase in the number of patients with ESRD without diabetes mellitus (DM) requiring dialysis therapy leads to increased interest and the need to study carbohydrate status in these patients. It is known that hyperglycemia in patients without DM on hemodialysis (HD) is a predisposing factor to the development of cardiovascular accidents that worsen the quality of life and also increase mortality. The peculiarities of glucose metabolism in patients receiving RRT do not always allow adequate assessment of carbohydrate status using glycated hemoglobin (HbA1c). The review provides up-to-date information on the prevalence of DCM in patients with ESRD without DM receiving HD RRT, touches upon the peculiarities of glucose metabolism, interpretation of HbA1c and glycated albumin values, and mortality risk in hemodialysis patients with various DCM.